The image of the forest in the language picture of Olga Kobylyanskaya and Ulyana Kravchenko’s artistic worlds - Литвин, Олена Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The image of the forest has been characterized and the specific of its realisation in the language picture of Olga Kobylyanskaya and Ulyana Kravchenko artistic worlds has been analysed the role of this image in the poetic text has been found out. The tropes with the nomenon forest have been researched it has been proved that these tropes are the characteristic feature of the writers language art. The art of Olga Kobylyanskaya and Ulyana Kravchenko as well as the art of any other writer can’t be considered well known up to the end, because each researcher presents his own opinion either on this or that problem or this or that phenomenon. Because of this there is a need to do an analysis of the nomen’s forest functions in the language Olga Kobylyanskaya and Ulyana Kravchenko’s works, which is presented in the language of both writers artistic texts. The characteristic of the nomen forest will lead to the understanding of the deep processes of the lexical development in the modern Ukrainian language.